2021
DOI: 10.1096/fasebj.2021.35.s1.00277
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of particulate and emissions from 3 dimensional (3D) printers: Effects on the olfactory bulb (OB) and hypothalamic‐pituitary‐endocrine axes

Abstract: There is increasing concern regarding the potential health effects associated with exposure to plastic nanoparticles and the chemicals released when plastic is heated or dissolved in water. Although exposure to plastic particles and their composite chemicals can be generated by a number of different processes, 3D printers used in manufacturing, schools and homes, are sources of fumes and particulate that humans are exposed to. This study examined whether inhalation of particulate and fumes generated during 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…While particles were consistently emitted during each test, a mean particle diameter of 50–60 nm confirmed the majority of the particles emitted were ultrafine particles. A marked increase in emissions from the 3D printer was observed as printing began with all filaments, consistent with the emissions profile outlined in earlier studies [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…While particles were consistently emitted during each test, a mean particle diameter of 50–60 nm confirmed the majority of the particles emitted were ultrafine particles. A marked increase in emissions from the 3D printer was observed as printing began with all filaments, consistent with the emissions profile outlined in earlier studies [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Resultssupporting
confidence: 89%
“…However, the generation of UFPs and NPs is not confined to these materials alone [ 1 , 2 , 3 ]. Several in vitro and in vivo studies have indicated that NPs can induce acute lung inflammation [ 4 , 5 , 6 , 7 ]. One human case report highlighted that a 28-year-old worker developed work-related asthma ten days after operating ten FDM 3D printers with ABS filaments in a 3000 cubic feet work zone [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations